Galhas entomógenas de Miconia prasina (Sw.) DC (Melastomataceae) em remanescentes de Floresta Atlântica Nordestina. (Lundiana: International Journal of Biodiversity, 2006)
The objective of this work was to describe the morphology of the insect galls occurring in Miconia prasina (Melastomataceae) and their yearly frequencies in four remnants of Atlantic forest in northeastern Brazil. In each study area young individuals up to 2 m were marked and observed monthly for the number of galls. The leaf-galling insects induced elliptic, spherical and fusiform types in the leaf blade of M. prasina growing at four studied fragments; a cylindrical type in Refúgio Charles Darwin; and a piriform type in the axillary bud in the Cachoeira and Capoeirão fragments. In the selected individuals 1131 new galls were counted along a year. Of these, 548 were elliptic, 336 spherical, 125 fusiform, 81 cylindrical and 41 piriform. The gall inductors were generally registered in larger numbers in the most humid months. The results of this study contribute to increase the knowledge of Neotropical galls diversity.